Effect of Ramadan Fasting on Sex Hormones in Infertile Male - Al-Chalabi, Sajeda (Tikrit Journal of Pharmaceutical Sciences, 2023)
Ramadan fasting is one of the 5 pillars of Islam and one of the most significant Ibadat (worships) of Islam. Throughout the world, millions of Muslims fast during Ramadan to fulfill this religious obligation. Aims: The aim of the study is to determine changes in the serum concentrations of gonadotropins, testosterone and prolactin hormones in infertile males after fasting of Ramadan and whether fasting improves fertility in the male. Participants and Methods: This is a case series study was conducted on 54 infertile male subjects aged (25-50 years) who fasted during Ramadan. Two blood samples were taken from each patient, one before and the other after fasting of Ramadan. Serum FSH, LH, prolactin and testosterone measurement was done by using Enzyme Linked Immune Sorbent Assay (ELISA). Results: There was no significant difference in serum FSH, LH, prolactin hormones when we compared them before and after Ramadan fasting. Concerning serum testosterone hormone, there was a decrease in its level after fasting but not reach significance when compared with its level before fasting. Conclusion: Serum levels of FSH, LH, prolactin and testosterone were unchanged after fasting of Ramadan.